Analysis of the Effectiveness of PDKB Performance on SAIDI SAIFI at PT. PLN UP3 Langsa - is, muh azir (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
Maintaining reliability in the distribution of electricity to customers or the public can be achieved through electrical maintenance. In the SUTM network, maintenance often involves power outages during work, resulting in losses for both consumers and the company because kWh cannot be distributed. Maintenance without power outages can be carried out by the PDKB team, who perform work on network development or installations while the system is energized. This study aims to determine the values of SAIDI and SAIFI, and the amount of kWh before and after the implementation of PDKB at PT. PLN (Persero) UP3 Langsa. Data collection involved observation techniques and analysis of kWh, SAIDI, and SAIFI values. The research results show that maintenance with PDKB can save 1,457,823.97 kWh for customers, generating Rp. 1,135,391,541.48. The SAIDI value is 819.456 Minutes/Customer and the SAIFI value is 9.29 times/customer. In contrast, maintenance without PDKB yielded a kWh value of 3,921,103.2 and a rupiah value of Rp. 3,136,882,560. The SAIDI value is 1533.84 Minutes/Customer and the SAIFI value is 10.04 times/customer. This indicates that the smaller the SAIFI and SAIDI values, the better the service provided by PLN to customers, thereby improving the company's image and avoiding losses due to discontinuity in electricity distribution services.Keywords: PDKB, SAIDI, SAIFI